GAMBARAN TINGKAT PENGETAHUAN AKSEPTOR KB SUNTIK TENTANG EFEK SAMPING DMPA (DEPO MEDROXY PROGESTERON ASETAT) DI KELURAHAN KALIBEBER KECAMATAN MOJOTENGAH KABUPATEN WONOSOBO - Nugraheni, Nazilla; Alviana, Fifi (Jurnal Ilmiah Kesehatan, 2020)
Purpose: This is to describe the knowledge of injecting family planning acceptors about the sideeffects of DMPA in Kalibeber Mojotengah VillageMethods: :Descriptive research with cross sectional approach. Sampling technique withaccidental sampling. In this study, 66 active DMPA family planning acceptors were determinedin Kalibeber Village, Mojotengah District, Wonosobo RegencyResults:The level of knowledge of family planning acceptors about the side effects of DMPAinjection family planning was good, namely 36 respondents (54.5%). Based on the level of basiceducation, most of the acceptors have good knowledge. 18 respondents (47.4%) In informalwork, some have good knowledge, 51 respondents (54.9%) Most of the respondents who havegood knowledge get information from health workers 27 Respondents (51.9%) %), healthworkers (51.9%). Conclusion: Health workers have an important role in the knowledge of family planningacceptors.